2018
DOI: 10.1111/desc.12717
|View full text |Cite
|
Sign up to set email alerts
|

Developmental patterns of change in the influence of safe and risky peer choices on risky decision‐making

Abstract: Adolescents take more risks when peers monitor their behavior. However, it is largely unknown how different types of peer influence affect adolescent decision-making. In this study, we investigate how information about previous choices of peers differentially influences decision-making in adolescence and young adulthood. Participants (N = 99, age range 12-22) completed an economic choice task in which choice options were systematically varied on levels of risk and ambiguity. On each trial, participants selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
72
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 42 publications
11
72
3
1
Order By: Relevance
“…Past studies using lottery tasks with unknown outcome probabilities suggest that uncertainty tolerance decreases from adolescence to adulthood 16,17 . One study found that adolescents are more uncertainty tolerant than children and adults 18 (but see 19,20 ).…”
mentioning
confidence: 99%
“…Past studies using lottery tasks with unknown outcome probabilities suggest that uncertainty tolerance decreases from adolescence to adulthood 16,17 . One study found that adolescents are more uncertainty tolerant than children and adults 18 (but see 19,20 ).…”
mentioning
confidence: 99%
“…Recent studies support the idea that directly observing and copying others can explain at least some of these social influence effects, and that social influence may be stronger in younger individuals than in adults (Blankenstein et al, 2016;Braams et al, 2019;Simon Ciranka & van den Bos, 2019;Foulkes et al, 2018;Gardner & Steinberg, 2005;Knoll et al, 2015;Smith et al, 2014). Notably, social influence has previously shown to be stronger for safety-promoting than for risky behaviour for most individuals (Braams et al, 2019;Simon Ciranka & van den Bos, 2019) in confined experimental settings. However, these experiments addressed only part of the complex dynamics of social influence, leaving several questions unanswered.…”
Section: Discussionmentioning
confidence: 72%
“…Experimental evidence suggests that adolescents are more likely than members of other age groups to directly copy observed peer behaviour (Blankenstein et al, 2016;Braams et al, 2019;. It is not known whether adolescents are also NORMS IN ADOLESCENT RISK ENGAGEMENT 4 more likely to actively encourage risk-taking, or whether they are more sensitive to perceived risk-norms (in absence of overt peer behavior) than are people of other ages.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about the previous decisions of others in a similar situation can influence whether we judge it acceptable to drive. Prior experimental studies have shown that people are prone to follow previous decisions of others (Albert, Chein, & Steinberg, 2013;Blankenstein et al, 2016;Braams et al, 2019;Hoorn, Fuligni, Crone, & Galvan, 2016).…”
Section: Social Contextmentioning
confidence: 99%
“…Previous work has shown that information about others' choices has a robust influence on decision making. Seeing information about others' previous choices makes one more likely to also select that option, an effect seen in the more safe (Braams, Davidow, & Somerville, 2019) as well as the more risky direction (Chung, Christopoulos, King-Casas, Ball, & Chiu, 2015). In this study, we investigate how seeing information about others' previous choices specifically affects attitudes towards risk and ambiguity.…”
mentioning
confidence: 99%